BUSINESS SOCIAL RESPONSIBILITY AND “GREEN INNOVATIONS” – CAUSE-AND-EFFECT RELATIONSHIP - Mzevinar Nozadze; Giorgidze Badri; Kapanadze Maia (International Journal of Innovative Technologies in Social Science, 2025)
At the present stage of society development, one of the global problems is the transition to sustainable and inclusive development and regulation of related issues. The purpose of the study is to determine the role of corporate social responsibility in relation to sustainable development measures and environmental protection. The study also emphasizes that the government has traditionally been the main subject of environmental protection measures, although in recent years the issue of business participation has become increasingly visible in the international sustainable development agenda. Particular attention is paid to financial and credit institutions, with the support of which innovative, environmentally friendly financial instruments are introduced and distributed in the financial markets of various countries. Thus, the more effectively and extensively business entities use innovative financial instruments related to green projects, the more the social value of their activities will increase. As a result of the study, recommendations were formulated indicating methods for optimizing the social responsibility of business entities in terms of implementing environmental policies.